INTEGRATION OF ECOLOGICAL PRINCIPLES IN THE PESANTREN SYSTEM: A STUDY OF SUSTAINABILITY AND ENVIRONMENTAL CONSERVATION PRACTICES IN ISLAMIC EDUCATION - Rohmah, Fitri Nur (Molang: Journal Islamic Education, 2024)
While pesantren education in Indonesia has great potential in implementing ecological principles, challenges in integrating environmental values often hinder its effectiveness. This study explores how ecological principles are incorporated into the pesantren education system and their impact on environmental conservation practices and awareness of santri. Data were collected through in-depth interviews, participatory observation, and document analysis using a qualitative approach with a descriptive-analytical method. The findings show that ecological principles can be effectively implemented through a holistic approach combining Islamic values with conservation practices. The results reveal that this integration increases environmental awareness among santri and strengthens their Islamic identity as khalifahs responsible for the ecosystem. This research enriches the theory of ecological integration in Islamic education and provides a model that can be applied in other pesantren. Practical implications include guidance for pesantren managers in designing effective environmental curricula and activities. This research also opens pathways for further studies with quantitative or mixed-methods approaches and exploring digital technology in pesantren ecological education.